A phenotypically severe, biochemically "silent" case of HIBCH deficiency in a newborn diagnosed by rapid whole exome sequencing and enzymatic testing. Issue 4 (5th February 2020) - D'Gama, Alissa M.; Brucker, William J.; Zhang, Tian; Gubbels, Cynthia S.; Ferdinandusse, Sacha; Shi, Jiahai; Grant, Patricia Ellen; VanNoy, Grace; Genetti, Casie A.; Juusola, Jane; Yu, Timothy W.; Kritzer, Amy; et al.
Abstract: 3‐Hydroxyisobutyryl‐CoA dehydrogenase (HIBCH) deficiency is a rare error in valine catabolism associated with a Leigh syndrome‐like phenotype, mitochondrial dysfunction, and increased C4‐OH. We report the most severe case to date in a full‐term female who presented with poor feeding and nystagmus on day of life (DOL) 1. Although initial neuroimaging findings were concerning for metabolic disease, further metabolic testing was nondiagnostic and she was discharged on DOL 18. She was readmitted on DOL 22 after severe apneic episodes requiring intubation, with EEG demonstrating multifocal seizures and MRI/MRS demonstrating worsening findings. Care was withdrawn DOL 27 and she expired. Rapid whole exome sequencing (WES) demonstrated compound heterozygous variants in HIBCH with a paternal pathogenic variant (c.852delA, p.L284FfsX10) and a maternal likely pathogenic variant (c.488G>T, p.C163F). Fibroblast enzymatic testing demonstrated marked reduction in HIBCH levels. This case demonstrates the importance of rapid WES and follow‐up functional testing in establishing a diagnosis when metabolic disease is suspected but lacks an expected biochemical signature.